Financial Mangement Through Socialization of Transaction Recording and Cash Flows in Gili Barat: Array - Solihah; Fathul Qorib; Yusfila (Lembaga Citra Pustaka, 2022)
The COVID-19 pandemic has a significant impact on the economy, even reaching minus 0.74%. This has caused various economic institutions to experience a crisis, the UMKM sector is one of the economic sectors that is able to survive during the pandemic. It is proven by the large number of UMKM actors. However, behind the relatively large number, most UMKM actors still do not have the ability to manage financial matters. Therefore, the community service of Trunojoyo Madura University carries out a work program of financial management socialization regarding transaction recording and cash flow preparation. This activity was carried out in the Gili hamlets with three series of activities, the first was the manufacture of hidden peanut products, the second was information on the importance of financial management in business and transaction recording, and the third was socialization of cash flow preparation. With the implementation of this activity, it is hoped that it will be able to improve economic conditions in the village of Gili Barat after the Covid-19 pandemic.